Analysis of ocular toxicity of fluconazole and voriconazole eyedrops using HET-CAM - A. Fernández-Ferreiro; M. González Barcia; M. Gil Martínez; J. Blanco Mendez; M. J. Lamas Díaz; F. J. Otero Espinar (Farmacia Hospitalaria)
Abstract: Purpose: The objective of the study is to provide toxicological information through the HET-CAM test of Fluconazole and Voriconazole eye drops prepared commonly in Pharmacy Servi - ces for the treatment of fungal keratitis. Method: Experimental Study. The ocular toxicity of topical voriconazole 10 mg/ml and fluconazole 2 mg/ml were evalua ted by the hen‘s egg test (HET) on the chorioallantoic membrane (CAM). The effects on blood vessels were based on its behavior during 300 seconds and processes that may occur at each time, then we calculated the irritation index (is, irritation score). Results and conclusions: Both eye drops, voriconazol and fluconazole have been proven to be safe, since the IS that we obtained was zero for both samples and did not present significant signs of irritation. Therefore, these eyedrops are conside red suitable for ocular use from a toxicological point of view.